Chemical kinetics properties and the influences of different hydrogen blending ratios on reactions of natural gas. (January 2023) - Dong, Hongtao; Li, Runzhi; Zhao, Wenbin; Zhang, Yansong; Chen, Xu; Zhang, Qi; Cao, Mengting; Liu, Fengyuan
Abstract: Hydrogen is blended with natural gas to form hydrogenated natural gas (HCNG), which is a new, efficient and clean energy. CHEMKIN-PRO 19.0 software was combined with the GRI-Mech 3.0 mechanism to evaluate the capacity of H2 blending in reducing CO and CO2 emissions. Influences of H2 blending on combustion reactions of the CH4 -air mixture were investigated. The results showed that the main reactants and products (CH4, CO, and CO2 ) decreased in gradient with increasing H2 blending ratio, accompanied by a shorter reaction duration and a faster reaction rate. After adding H2, important key radicals H, O, and OH increase significantly, so that the combustion reactions become more violent. Sensitivity analysis reveals that among relevant elementary reactions of CO and CO2, R38 (with its promotional effect) and R158 (with its inhibitory effect) show the greatest sensitivity. As the H2 concentration increases, the sensitivity of the two reactions (separately with promotional and inhibitory effects) decreases. Blending H2 in the natural gas can improve the combustion rate and reduce the generation of emissions CO and CO2, which is of important significance for realizing low-carbon goals and reducing air pollution.